Medical Quiz: Images Vol.7(2) - Samad, Tabassum; Rahim, Muhammad Abdur; Saha, Shudhanshu Kumar; Ul Haque, Wasim Md Mohosin (BIRDEM Medical Journal, 2017)
Abstract not available Birdem Med J 2017; 7(2): 172